Evolution of Intestinal Microbiota of Asphyxiated Neonates Within 1 Week and Its Relationship With Neural Development at 6 Months - Zhang, Xiaojiao; Liu, Lili; Bai, Wei; Han, Ying; Hou, Xinlin (Frontiers in Pediatrics, 2021)
Introduction: Asphyxia is an emergent condition in neonates that may influence the function of the nervous system. Research has shown that intestinal microbiota is very important for neurodevelopment. Studies regarding the association between gut microbiota and neurodevelopment outcome in asphyxiated newborns remain scarce. Objective: To study the microbial characteristics of asphyxiated neonates within 1 week of life and to investigate their relationship with neural development at 6 months. Methods: The feces produced on days 1, 3, and 5, and the clinical data of full-term neonates with asphyxia and without asphyxia, delivered from March 2019 to October 2020 at Peking University First Hospital, were collected. We used 16S ribosomal deoxyribonucleic acid amplicon sequencing to detect the intestinal microbiota of asphyxiated neonates and neonates in the control group. We followed up asphyxiated neonates for 6 months and used the Ages and Stages Questionnaires-3 (ASQ-3) to evaluate their development. Results: A total of 45 neonates were enrolled in the study group and 32 were enrolled in the control group. On day 1, the diversity and richness of the microflora of the study group were more than those of the control group. Non-metric multidimensional scaling analysis showed significant differences in the microbiota of the two groups on days 1, 3, and 5. At the phylum level, the main microflora of the two groups were not different. At the genus level, the study group had increased relative abundance of Clostridium_sensu_stricto_1, Lachnoclostridium, Fusicatenibacter, etc. on day 1. On day 3, the relative abundance of Clostridium_sensu_stricto_1, Fusicatenibacter, etc. was still greater than that of the control group, and the relative abundance of Staphylococcus was less than that of the control group. On day 5, the relative abundance of Clostridium_sensu_stricto_1 and Lachnoclostridium was still higher than that of the control group, and the relative abundance of Dubosiella in the study group was significantly increased. At the species level, on day 3, the relative abundance of Staphylococcus caprae in the study group was less than that in the control group. Linear discriminant analysis effect size showed that the microbiota of the study group mainly consisted of Lachnospiraceae and Clostridia on day 1 and Clostridia on day 3. In the control group, Staphylococcus was the dominant bacterium on day 3. Neonates in the study group were followed up for 6 months, and the communication score of ASQ-3 was negatively correlated with the relative abundance of Lachnospiraceae and Clostridia on day 1. Conclusion: The diversity and richness of the microbiota of asphyxiated neonates on the first day of life were significantly increased and mainly consisted of pathogenic flora. Lachnospiraceae and Clostridia found in neonates with asphyxia on day 1 of life may be related to neural development at 6 months.